(untitled) (Journal Of Educational and Psychological Researches, 2022)
There have been many negative phenomena in Iraqi society, especially after the political crises over the last years, such as the spread of violence, the deterioration of the economic situation, the spread of unemployment and poverty, and the disintegration of social ties, divorce, and the entry of the scourge of drugs. Among the most dangerous of these emergent phenomena, the phenomenon of suicide among young people of both sex, which has grown and increased in an unprecedented manner, surpassing all known social norms in Iraqi society and the prevailing religious values. Suicide in Iraqi society has transformed from a simple case to a visible presence in all Iraqi provinces. Suicides cases have registered in all cities of Iraq and of both sex and in different age groups have increased in an unprecedented manner due to social problems and unemployment, economic, social, and psychological reasons for committing suicide. The sociological experts have confirmed that the political reasons are behind all the above reasons, but they have contributed largely to create these reasons.